The adsorption of amitriptyline and nortriptyline on activated carbon, diosmectite and titanium dioxide - Roman Maršálek; Martin Švidrnoch (Environmental Challenges, 2020)
The adsorption of the tricyclic antidepressants amitriptyline and nortryptyline was studied. Activated carbon, diosmectite and nano-sized titanium dioxide were selected as adsorbent materials. After monitoring the effect of contact time on the amount adsorbed, it was determined that the adsorption kinetics follow a pseudo-second kinetic equation. The system reached equilibrium more rapidly in the case of nortryptyline adsorption compared to amitryptyline. After evaluation of the adsorption isotherms, it was stated that the adsorption in the case of amitriptyline better corresponds to the Freundlich model, on the contrary, the adsorption of nortryptyline can be described by the Langmuir model. The adsorption of amitriptyline on all three adsorbents was approximately twice as high as that of nortryptyline. Activated carbon has the highest adsorption capacity for both drugs. The specific adsorption capacities are as follows. For amitriptyline: activated carbon 3.75 mmol g−1, diosmectite 3.30 mmol g−1, titanium dioxide 2.97 mmol g−1; for nortriptyline: activated carbon 1.87 mmol g−1, diosmectite 1.82 mmol g−1, titanium dioxide 0.79 mmol g−1. In addition, the zeta potential of the individual adsorbent materials was also monitored depending on the pH and the amount of antidepressants absorbed. pH and ionic strength significantly affect the critical micellar concentration of antidepressants. This is subsequently reflected in the different adsorption behavior of amitriptyline and nortryptyline.